Analisis tentang Problematika Penegakan Hukum terhadap Pelaku Tindak Pidana Narkotika - Anisa Nazaila Idris; Mahfudzah Rahva Nur Laily; Syarifuddin, Syarifuddin (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Law enforcement against narcotics crimes in Indonesia faces various complex problems, both from legal aspects, institutional structure, and community legal culture. Even though Law Number 35 of 2009 concerning Narcotics has been enacted, the circulation and abuse of narcotics is still increasing every year. This study aims to analyze problems in law enforcement against perpetrators of narcotics crimes and identify the factors that affect them. The research method used is normative juridical with a legislative approach and a case approach. The results of the study show that the main obstacles lie in the lack of coordination between law enforcement agencies, weak integrity of the apparatus, overlapping regulations, and low public legal awareness. In addition, the limitation of supporting facilities and infrastructure such as rehabilitation facilities, forensic laboratories, and early detection technology also hinders the effectiveness of case handling. The high modus operandi of increasingly sophisticated narcotics networks is also a challenge for the authorities. Therefore, strengthening regulations, increasing the capacity of human resources, utilizing modern technology, and more intensive collaboration between agencies need to be optimized as a comprehensive effort to strengthen the effectiveness of law enforcement in the narcotics sector.